Distal protection filter device efficacy with carotid artery stenting: comparison between a distal protection filter and a distal protection balloon - Iko, Minoru; Tsutsumi, Masanori; Aikawa, Hiroshi; Matsumoto, Yoshihisa; Go, Yoshinori; Nii, Kouhei; Abe, Gorou; Ye, Iwae; Nomoto, Yasuyuki; Kazekawa, Kiyoshi (Japanese journal of radiology, 2013)
Purpose This retrospective study aimed to compare the effectiveness of the embolization prevention mechanism of two types of embolic protection device (EPD)—a distal protection balloon (DPB) and a distal protection filter (DPF). Methods Subjects were 164 patients scheduled to undergo carotid artery stenting: a DPB was used in 82 cases (DPB group) from April 2007 until June 2010, and a DPF was used in 82 cases (DPF group) from July 2010 to July 2011. Rates of positive findings on postoperative diffusion-weighted imaging (DWI) and stroke incidence were compared. Results Positive postoperative DWI results were found in 34 cases in the DPB group (41.4 %), but in only 22 cases in the DPF group (26.8 %), and there was only a small significant difference within the DPF group. In the DPB group, there was one case of transient ischemic attack (TIA) (1.2 %) and four cases of brain infarction (2 minor strokes, 2 major strokes; 4.9 %), compared to the DFP group with one case of TIA (1.2 %) and no cases of minor or major strokes. Conclusions In this study, significantly lower rates of occurrence of DWI ischemic lesions and intraoperative embolization were associated with use of the DPF compared to the DPB.